AB0687 THE PROBABILITY OF SPONDYLОARTHRITIS IN PATIENTS WITH UVEITIS. (2nd June 2020) - Godzenko, A.; Razumova, I.; Guseva, I.
Abstract : Background: Uveitis is a heterogeneous group of inflammatory eye diseases, some of which may be associated with spondyloarthritis (SpA). The probability of SpA depends on the clinical features of uveitis. Objectives: To evaluate the probability of SpA depending on the clinical features of uveitis. Methods: 208 patients with uveitis referred from ophthalmologists were assessed at the Institute of Rheumathology. 139 of 208 pts had an acute recurrent course of uveitis, 69-chronic course; 149 of 208 had isolated anterior uveitis, 59 – panuveitis involving the posterior and/or intermediate part of the eye; 160 had unilateral uveitis, 48 – bilateral; 106 had HLA- В27, 102 - without HLA-В27. In addition to HLA- В27, a survey was performed to identify clinical and imaging signs of SpA, including radiography and MRI of sacroiliac joints. In 60 cases (28.8%), various SpA were identified (20 –ankylosing spondylitis, 2- reactive arthritis, 38 – non-radiographic SpA). In 148 pts SpA was not confirmed (4 of them had Behcet ' s disease, 2-sarcoidosis, 4-toxoplasmosis, 29 - viral uveitis, 1 - Fux syndrome, 2 – Vogt-Koyanagi- Harada syndrome, 2 - multiple sclerosis, 104 – unspecified uveitis). Sensitivity (Se) and specificity (Sp), relative risk (RR), 95% confidence interval (CI), and likelihood ratio (LR) were calculated for each clinical parameter of uveitis with the following assessment of the probability of SpA. Results: Pretest probability of SpA in the group was 28.8%, that corresponds to pretest odds of 0.4. Among 139 pts with acute recurrent uveitis SpA was identified in 45 (32.3%), among 69 with chronic uveitis – in 15 (21.7%), RR-1.49, 95% CI [0.896, 2.475], LR-1.17. Among 149 pts with isolated anterior uveitis SpA was in 55(36.9%), among 59 with panuveitis – in 5(8.5%), RR=4.36, 95% CI [1.8, 10.3], LR-1.43. In a subgroup of 160 pts with unilateral uveitis SpA diagnosed in 51 (31.9%), in a subgroup of 48 with bilateral uveitis – in 9 (18.7%), RR = 1.7, 95% CI [0.9, 3.1], LR-1.14. Among 160 HLA-B27-positive pts SpA detected in 56 (52%), among 102 HLA-B27- negative – in 4 (3.9%), RR=13.4, 95% CI [5.1, 35.8], LR-2.7. Taking into account the pretest odds and likelihood ratio of all parameters, posttest odds was 2.7, that corresponds to posttest probability of 67%. Conclusion: A combination of such signs of uveitis as isolated localization in the anterior part of the eye, acute recurrent course, unilateral inflammation, HLA-B27, increases the probability of SpA more than 2 times References: [1]Sykes M, Hamilton L, Jones C. et al. Prevalence of axial spondyloarthritis in patients with acute anterior uveitis: a cross-sectional study utilising MRIRMD Open. 2018 Feb 24;4(1):e000553. doi: 10.1136/rmdopen-2017-000553. eCollection 2018. [2]Bubová K., Gregová M., Zegzulková K. et al. Active sacroiliitis on magnetic resonance imaging in patients with anterior uveitis. Ann Rheum Dis. 2019; 78(2): A470. https://doi 10.1136/annrheumadis-2019-eular7439 . Disclosure of Interests: None declared